Prejudice And Stereotypes In Innaritu's Babel Movie(2006):A Social Psychological Perspective - YUNIARDI, FAJAR (2012)
The researcher analyzes prejudice and stereotypes in Innaritu's Babel movie. The researcher analyzes the prejudices and stereotypes each characters in Babel movie based on gender, ethnicity, place and intensity. The objective of the study is to analyze the movie based on its structural analysis and based on social psychological analysis. This study is a qualitative study. The object of the study is Alejandro Gonzales Innaritu's Babel movie released in October 27,2006 in USA by Paramount picture.The data sources are divided into two, namely primary data source and secondary data source.The primary is the movie itself and the secondary data source is other sources related to the analysis such as the author biography, books of literary theory and also psychology books, particularly related to social psychological books. The method of data collection is library research. The technique of data analysis is descriptive analysis. The results of the study are as follows. First, Alejandro Gonzales Innaritu's Babel movie was presented is social construction which is determined by the culture that was illustrated on the characters, characterization, narration or dialog. Second, Gonzalez Innaritu succeeded to show the reality of human life through his movie, especially social relations that appear in society between the wester and Moslem country including of prejudices and stereotypes that influence on social psychology of person.